The payout behaviour of German savings banks - Matthias Köhler (Deutsche Bundesbank, 2016)
Our analysis finds that despite the growing number, the majority of savings banks currently do not make any payouts. Furthermore, savings banks distribute only a small part of their net profit to the shareholders. This means that they can still build up capital even if they make payouts. Savings banks also hold significantly more capital than is called for by the regulatory framework. Finally, the regression analysis shows that savings banks that have less capital distribute profits to their shareholders considerably less frequently. This correlation has intensified since 2009, even though the Savings Banks Acts (Sparkassengesetze) were relaxed in individual federal states. All in all, our results therefore indicate that payouts do not currently pose a threat to the capital adequacy of most savings banks.
Keywords: G21; G29; G35; 330; savings banks; distributions; capital adequacy